Spiritual aspects of living with infertility: A synthesis of qualitative studies - TIMMINS, FIONA (My University, 2017)
Aims and objectives: To identify the spiritual aspects of patients experiencing infer- tility and seek a deeper and broader meaning of the involuntary childlessness expe- rience. Background: Infertility can be the cause for a spiritual crisis among some couples. Those who endure this involuntary childlessness condition frequently experience contradictory feelings and needs. In this context, core aspects of spirituality such as meaning and purpose in life are often questioned. Design: A review and synthesis of qualitative empirical research was undertaken to seek a deeper understanding of the spiritual aspects of patients’ experiences of infertility. Methods: An aggregative synthesis was conducted according to Saini and Shlonsky (Systematic synthesis of qualitative research, 2012, Oxford University Press, Oxford), using thematic analysis. Results: A total of 26 studies included female, male and couples. Settings revealed interviewees in different infertility phases such as diagnosis, assisted reproductive technologies and following fertility treatments. Two main themes emerged: spiritual needs and spirituality as a coping resource for infertility. Conclusion: Infertility affects the holistic existence of the couples. This adversity awakens spiritual needs along with unmet needs of parenthood. Coping strategies incorporating spirituality can enhance the ability of couples to overcome childless- ness and suffering. Relevance to clinical practice: Infertile couples’ experiences of infertilit y may offer an opportunity for s piri tual care particularly related to the assessment of spiritual needs and the promotio n of spiritual coping st rategies . Ef fective holistic care should support couples in overcoming and finding meaning in this life and hea lth conditio n.
PUBLISHED
Keywords: fertility, holistic care, midwifery, nursing, spirituality; fertility, holistic care, midwifery, nursing, spirituality